Hyperthyroidism Prevalence in China After Universal Salt Iodization - Wang, Chuyuan; Li, Yongze; Teng, Di; Shi, Xiaoguang; Ba, Jianming; Chen, Bing; Du, Jianling; He, Lanjie; Lai, Xiaoyang; Li, Yanbo; Chi, Haiyi; Liao, Eryuan; et al. (Frontiers in Endocrinology, 2021)
Background:Universal salt iodization (USI) was implemented in mainland China in 1996. The prevalence of hyperthyroidism and its risk factors now require examination. Methods: Data were acquired from a nationwide thyroid, iodine, and diabetes epidemiological survey (TIDE 2015–2017) of 78,470 subjects from 31 provinces. Iodine status, and thyroid hormones and antibodies were measured. Results:After two decades of USI, the prevalence of overt hyperthyroidism(OH), Graves’ disease (GD), severe subclinical hyperthyroidism (SSCH), and mild subclinical hyperthyroidism(MSCH)in mainland China was 0.78%, 0.53%, 0.22%, and 0.22%, respectively. OH and GD prevalence were higher in women than in men (OH: 1.16% vs. 0.64%, P<0.001; GD: 0.65% vs. 0.37%, P<0.001).Prevalence was significantly decreased after 60 years-of-age compared with 30–39 years-of-age (OH:0.61% vs. 0.81%, P<0.001; GD: 0.38% vs. 0.57%, P<0.001).Excessive iodine（EI）and deficient iodine (DI) were both related to increased prevalence of OH (odds ratio [OR] 2.09, 95% confidence interval [CI] 1.68–2.59; OR1.35, 95%CI 1.07–1.72, respectively); however, only DI was associated with increased prevalence of GD (OR1.67, 95%CI 1.30–2.15). Increased thyroid peroxidase antibody and thyroglobulin antibody levels were significantly associated with prevalence of OH and GD, but not SSCH and MSCH.Although hyperthyroidism was more prevalent in women, the association disappeared after adjusting for other factors such as antibody levels. Conclusion:OH and GD prevalences in mainland China are stable after two decades of USI.Iodine deficiency, elevated thyroid antibody levels, and middle age are the main risk factors for OH and GD. The SSCH population, rather than the MSCH population, shows similar characteristics to the OH population.